2021
DOI: 10.1177/2050312121989636
|View full text |Cite
|
Sign up to set email alerts
|

Cataract and associated factors among adults visiting ophthalmic clinic at Debre Markos comprehensive specialized hospital, northwest Ethiopia, 2020

Abstract: Introduction: Globally, it is estimated that 2.2 billion people have a visual impairment, of which around 65.2 million is due to cataract. Cataract is the leading cause of preventable blindness worldwide, with the greatest burden found in low-income countries. That is providing recent epidemiological data is very crucial to design intervention measures. The aim of this study was to assess the magnitude and associated factors of cataract among adults visiting ophthalmic clinic, Debre Markos comprehensive specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
2
7
2
Order By: Relevance
“…In our study, unmarried participants were 1.9 times more likely to have visually significant cataract than their married counterparts. This finding is in line with studies conducted in Debre Markos Hospital, 8 South Africa, 29 and multicenter studies in Kenya, the Philippines, and Bangladesh. 39 Unmarried status (widowed, divorced, and single) could lead to visually significant cataract owing to a lack of social support and having poor information concerning eye care services, including cataract surgery.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In our study, unmarried participants were 1.9 times more likely to have visually significant cataract than their married counterparts. This finding is in line with studies conducted in Debre Markos Hospital, 8 South Africa, 29 and multicenter studies in Kenya, the Philippines, and Bangladesh. 39 Unmarried status (widowed, divorced, and single) could lead to visually significant cataract owing to a lack of social support and having poor information concerning eye care services, including cataract surgery.…”
Section: Discussionsupporting
confidence: 91%
“… 26 This discrepancy could be attributed to differences in sociodemographic characteristics of the study populations as well as differences in study settings and availability and accessibility of cataract surgical services in the study areas. However, the prevalence in our study was lower than those in reported in Debre Markos Hospital, Ethiopia (57%), 8 Tamil Nadu (62.8%), 27 and Russia (44.6%). 28 These differences might be owing to variations in the study populations, sample sizes, and study areas.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations